Analisis Kelayakan Usaha Peternakan Tradisional Itik Petelur di Kabupaten Jember - Hariadi Subagja; Novi Pradita Erlina; Erfan Kustiawan (Jurnal Ilmu Peternakan Terapan, 2017)
This study aimed to determine how much income and business feasibility of duck laying farmers in Jember. The method used was a survey with 36 respondents duck laying farmers. The results of business feasibility analysis were B/C of 1.87, BEP (price) Rp983.27, BEP (production) 9,726.19 eggs, and ROI 55.70%. The laying duck business in several districts of Jember had incomes Rp656,408.00 (scale less than 100 ducks), Rp2,346,371.00 (scale 100 to 500 ducks), and Rp28,597,866.00 (scale more than 500 ducks).